O Limoeiro da educação: a história da criação da Diocese e a ação educacional de Dom Aureliano Matos em Limoeiro do Norte (1938-1968) - Vasconcelos Júnior, Raimundo Elmo de Paula (2006)
The centralization’s process of the Catholic Church’s leadership in Santa Sé in Rome, mainly after Republic’s Proclamation IN 1889 and the end of the clergyman in Brazil, produced the creation’s possibilities of more dioceses in the national territory, turning possible a better Brazilian ecclesiastic province’s administration. That process named Romanization. In this perspective, in 1938, was created one more diocese in Ceará. The history of the creation ant the choice of Limoeiro do Norte as the headquarter municipality of this new episcopate and the educational project of its first bishop, remain us to a local history’s research starting with a referential, that has as a grounding analysis a micro-history and the biography in historygraphical production; the oral history and the written source as methodological resources in the production of the historical knowledge, in a recognition’s contribution relationship of each other as a methodology and alternative or supplement one by another, don’t forgetting the reality of the world that surrounded the diocese. The thesis is structured in three chapters: in the firs, a general view about the instructional reality of Limoeiro do Norte city as the bishopric’s creation; the history of Limoeiro do Norte diocese’s creation and Dom Aureliano Matos biography. In the second chapter an analysis of the main written source: the six ministerial letters, most of them written by hand by Dom Aureliano Matos. The third chapter relates about an instructional action of Dom Aureliano Matos in Limoeiro do Norte, analyzing each institution created by himself. It’s an analysis point in this same chapter, in an evaluative spatial perspective, the changing of the municipality, in educational reference, in a downtown-suburb relationship with the other municipalities of Vale do Jaguaribe. Therefore the church and its alliances with other society sections, from the diocese’s creation in the Vale do Jaguaribe, turned possible the “Limoeiro of the Education.”